Sustainability assessment of precast Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) cantilever retaining walls - Nematollahi, Behzad; Muhammad Rashid, Raizal Saifulnaz; Voo, Yen Lei (Maxwell Science Publication, 2014)
This study evaluates the environmental impacts of a newly designed precast Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) cantilever retaining wall as a sustainable alternative approach compared with the conventional precast Reinforced Concrete (RC) cantilever retaining wall. Nowadays, according to the shocking reports of many researchers worldwide global warming is one of the most devastating problems of human being. To date, lots of research has been undertaken in the concrete industry to tackle this issue through reducing the environmental footprints of our structural designs. In this regard, UHPFRC technology offers substantial benefits through efficient use of materials as well as optimization of the structural designs resulting less CO2 emissions, Embodied Energy (EE) and Global Warming Potential (GWP). UHPFRC as a sustainable construction material is mostly appropriate for the use in the fabrication of precast members such as precast concrete cantilever retaining walls. This study demonstrates the overview of the designed precast concrete cantilever retaining wall manufactured from UHPFRC and its Environmental Impact Calculations (EIC) versus the conventional precast RC cantilever retaining walls. Based on the EIC results, the precast UHPFRC cantilever retaining walls are generally more environmentally sustainable than those built of the conventional RC with respect to the reduction of CO2 emissions, EE and GWP. In summary, the precast UHPFRC cantilever retaining wall proposed in this study is an alternative sustainable solution compared with the conventional precast RC cantilever retaining wall which can be used in many civil engineering projects.